Polymorphism of CD1B Gene and Its Association with Yolk Immunoglobulin (IgY) Concentration and Newcastle Disease Antibody Titer in IPB-D1 Chicken - M. F. Al-Habib; S. Murtini; A. Gunawan; N. Ulupi; C. Sumantri (Faculty of Animal Science, Bogor Agricultural University, 2020)
The CD1B gene has an important role in the immune system of poultry by mediating antibody induction. The study aimed to identify the CD1B gene polymorphism and its association with the concentration of IgY and ND antibody titers in IPB-D1 chicken. As many as 111 of IPB-D1 chickens at 21 weeks old were used in this study. Polymorphism identification of the CD1B gene was made using the PCR Sequencing method, while the IgY and ND antibody titers were done using the ELISA and HI test, respectively. The associations of gene polymorphism with IgY and ND antibody titers were analyzed using the General Linear Model (GLM) procedure and Duncan`s Multiple Range test. The results show that there are 4 SNPs in exon 3, i.e., c.550 G>A, c.562 T>A, c.588 A>G, and c.612 C>G. All the SNPs are missense, silent mutations, and polymorphic. The c.550 G>A and c.562 T>A SNPs were in Hardy Weinberg’s equilibrium and heterozygosity (0.054-0.252) condition, while the c.588 A>G and c.612 C>G SNPs were not in equilibrium and their heterozygosity was low (0.072-0.252). The combination of 4 SNPs generated 8 haplotypes, i.e., haplotypes 1, 2, 3, 4, 5, 6, 7, and 8. Haplotypes 1, 2, and 8 had high frequencies (17.6%-23.5%). The c.588 A>G and c.612 C>G mutations were significantly associated (p<0.05) with IgY concentration and c.562 T>A were significantly associated (p<0.05) with ND antibody titers. The haplotypes 2 and 8 with a combination of c.588 A>G and c.612 C>G mutations had higher IgY concentration and ND antibody titers (p<0.05) compared to the other haplotypes. In conclusion, this study has identified the CD1B gene as a polymorphic and is associated with IgY concentration and ND antibody titers in IPB-D1 chicken.